Adsorption Ability of Cephalexin onto the Straw-Based Activated Carbon: Performance and Mechanism - Tan, Lam Van; Nguyen Thi, Hong-Tham; Dao Thi, To-Uyen; Thuy Hong, Nguyen Thi (Asian Journal of Chemistry, 2020)
A straw-activated carbon has been successfully synthesized with the high BET surface area, at 494.9240 m2/g, which is perfectly suitable for the adsorption of cephalexin antibiotic from aqueous water. It is noted that the adsorption capacity of straw-activated carbon is demonstrated by the effect of initial concentration, contact time, pH solution and dosage. The straw- activated carbon exhibited improved decontaminant efficiency towards cephalexin antibiotics. Quick and improved sorption could be attributable to the distinctive structural and compositional merits as well as the synergetic contribution of functional groups to surface material. Most interestingly, the adsorption capacity achieved at pH 6 was ~98.52%. A mechanism adsorption has been proposed to demonstrate adsorption of the straw-activated carbon (AC-S). By comparison with other studies, it is confirmed that AC-S in this study obtained a higher removal efficiency than other adsorbent materials, suggesting that straw-activated carbon may be an appropriate candidate to treat cephalexin from wastewater media.